A Randomized, Controlled, 3-Arm Trial of Pharmacological Penile Rehabilitation in the Preservation of Erectile Function After Radical Prostatectomy. Issue 2 (7th December 2020) - Miranda, Eduardo P.; Benfante, Nicole; Kunzel, Brian; Nelson, Christian J.; Mulhall, John P.
ABSTRACT: Background: Although the concept of penile rehabilitation after radical prostatectomy (RP) has been advocated for decades, there is little definitive evidence regarding its utility or the best strategy to optimize patient outcomes. Aim: The goal of this study is to analyze the ability of 3 different pharmacological strategies to preserve the ability of men to achieve spontaneous (non-medication assisted) erections after bilateral nerve-sparing RP. Methods: This IRB- and FDA-approved study studied penile rehabilitation in a 3-arm fashion with a target enrollment of 200 patients. (i) Control arm: nightly placebo with sildenafil 100 mg on demand for sexual relations (up to 6 pills/month); (ii) nightly sildenafil arm: nightly sildenafil 50 mg and sildenafil 100 mg on demand for sexual relations (up to 6 pills/month); (iii) combination therapy arm: nightly sildenafil 50 mg (5 nights/week) plus intracavernosal injections twice/week. Inclusion criteria included bilateral nerve-sparing surgery, normal serum total testosterone, and good preoperative baseline erectile function as measured by the erectile function domain score of the IIEF (EFD) (≥24). Patients were followed with a medication use diary and the IIEF questionnaire at 6 weeks, 3 m, 6 m, 12 m, 18 m and 24 m. Outcomes: A difference was seen in the IIEF-EFD scores between the 3 groups at 24 months after RP. Secondary end points include the time to return of spontaneous functional erections, the time for patients to respond to oral erectogenic therapy, and the proportion of patients who have normalization of their IIEF-EFD scores. RESULTS: The study was interrupted because of failure to recruit the target study population in a reasonable timeframe. A total of 76 subjects with median age of 57 (IQR: 51, 63) years and mean IIEF-EFD of 29 (IQR: 27, 30) were initially randomized, but at 24 months, the sample sizes by group were (i) n = 4; (ii) n = 18; and (iii) n = 10, with median IIEF-EFD 24 (IQR: 18, 28), 24 (IQR: 18, 28), and 21 (IQR: 9, 26), respectively. There was no statistical difference among the groups in the final analysis. Clinical Implications: Definitive evidence for the ability of different pharmacological rehabilitation strategies to improve long-term EF outcomes might never be available. Strengths & Limitations: This was a well-designed randomized and 3-arm designed trial intended to provide decisive evidence regarding the utility of penile rehabilitation. Failure to recruit the target population is the main limitation. CONCLUSION: The limited number of patients in the present trial precludes definitive interpretation. However, results indicate how challenging it is to conduct true rehabilitation studies.